Women in Abu Tammam’s Artistic Experience - عيسى حكمت; جريكوس تيسير; العيسى حسام (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research presents the image of women in the life of Abu Tammam and his artistic experience through what Abu Tammam presented in his poetry library. It shows us that women occupy a prominent place in their artistic experience and have appeared in many ways.There is a beloved that the greatness of his travel and talk about it, is often a talk of self, and women who refuses to obey the poet’s desire because it will lead to the life of fainting and idle.We start by talking about the image of women as drawn by the poet in his verses, and his concept of true love as presented by the poet, and then we offer the concept of beauty of women in Abu Tammam and as presented by his hair and his position of gray,